Genealogical characteristics of children and adolescents with cholelithiasis and their families - O. V. Shutova,; N. V. Bahatska (Zaporožskij Medicinskij Žurnal)
One of the common pathologies of the hepatobiliary tract is cholelithiasis. The prevalence of this disease among children and adolescents is of particular concern.